2018
DOI: 10.3390/w10070907
|View full text |Cite
|
Sign up to set email alerts
|

The Suitability of Snow and Meteorological Conditions of South-Central Slovakia for Ski Slope Operation at Low Elevation—A Case Study of the Košútka Ski Centre

Abstract: In this study, the snow conditions of South-Central Slovakia (Inner Western Carpathians; temperate zone) were analyzed to assess the suitability for ski slope operations without snow production under 1000 m a.s.l. For the study site of the Košútka Ski Centre, meteorological conditions for snowmaking, snowpack characteristics, and snow water equivalent (SWE) compared with seasonal precipitation were identified. To identify the months suitable for snowmaking, the number of potential snowmaking days (PSD) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Snow water equivalent was calculated for each of the 96 points of snow course from snow depth and mean snow density identified in the particular survey. Technique of measuring the snow depth and density is described in more detail by Mikloš et al (2018a) and in general by, for example, López-Moreno et al (2013). In the first survey of the first three seasons, the depth of basal or bare ice layer was measured at 96 points of snow course.…”
Section: Soil Temperature and Characteristics Of Ski Piste Snowpackmentioning
confidence: 99%
See 4 more Smart Citations
“…Snow water equivalent was calculated for each of the 96 points of snow course from snow depth and mean snow density identified in the particular survey. Technique of measuring the snow depth and density is described in more detail by Mikloš et al (2018a) and in general by, for example, López-Moreno et al (2013). In the first survey of the first three seasons, the depth of basal or bare ice layer was measured at 96 points of snow course.…”
Section: Soil Temperature and Characteristics Of Ski Piste Snowpackmentioning
confidence: 99%
“…Our previous study (Mikloš et al, 2018a) showed that operability of low-elevation ski slopes in South-Central Slovakia is possible only with high snow production. Intensive snowmaking results in ski piste snowpack that is melting even a few weeks after disappearance of natural snow on the off-piste sites.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations